Designing of Air Conditioner System for College Laboratory - Rajneesh (International Journal For Research In Mechanical & Civil Engineering, 2018)
The use of air conditioning systems for residential/office buildings were very minimum in the earlier days of 1980’s. Due to the technology advancement and industrial growth buildings were started construction in a closed area and construction of apartment also increased after 1980’s with increased population. Also ambient temperatures are changed drastically due to pollution and concrete structure. Hence air conditioning has become an essential commodity for residential/office building. The increased demand of air conditioners has made scope for new innovations and technology developments in this field and hence there is lot of scope to study and learn this subject therefore the topic was chosen at most interest to develop our skills in this growing field. The necessity of design of air conditioning system for residential/office buildings is increasing day by day and lot of professionals have been developed in this field and adapted themselves into this field as consultants/designers due to the increased requirement. Hence we also felt necessity to learn this subject and upgrade our knowledge in this field of air conditioning. As a mechanical engineer we will do justification to this subject by putting our dedicated efforts using the project period and we will develop our technical skills in the field of air conditioning. The scope of work involved in this project is mainly divided into part A and part B. In part A–we will learn about the basic principles of thermodynamics which consists of thermodynamic processes, second law of thermodynamics from which subject of air conditioning is evolved. Also we will learn about principles of air conditioning which includes properties of gases and vapors, psychometric processes, properties of refrigerants, etc., In part B –we will learn the cooling load calculations, design calculations involved in selection of air conditioning systems and types of equipments and material of construction. This project has given opportunity for enrichment of our technical knowledge in the area of refrigeration and air conditioning and exposure to the practical field to learn the latest trends of air conditioning field and built our confidence to develop ourselves as a professional air conditioning engineer.